The Impact of Madrasah Digitalization Program on Strengthening Student Character: A Case Study at MA Ma'arif Al Muhtadi Lamongan - Hidayat, Rohmat; Ridlo, Husnur; Nashoih, Afif Kholisun; Anandita, Septian Ragil (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This qualitative study describes the implementation of a madrasah digitalization program and analyzes its impact on student character at MA Ma’arif Al Muhtadi Lamongan. Methodology/approach: Data were collected through observations, interviews, and documentation of e-learning, computer-based testing (CBT), electronic report cards, and digital attendance programs. Findings: The findings indicate that digitalization strengthens students' discipline, academic responsibility, and digital literacy as learning activities become more transparent and measurable. However, increased screen-based activity also triggers digital individualism and weakens everyday expressions of empathy Practical implications: Madrasahs must consciously integrate technology with Islamic moral values through value supervision, digital ethics guidance, and learning designs that intentionally cultivate empathy and social connectedness to balance digital competencies with students' affective development. Originality/value: This study addresses a gap in the literature by examining digitalization as a structured institutional program within an Islamic senior high school (Madrasah Aliyah) context, specifically focusing on late adolescents (11th-grade students), whereas previous studies predominantly focused on public schools.